Optimizing Promotional Strategies to Enhance Precious Metal Sales at PT. Pegadaian Talang Babat - Nopita Inriani; Nilfatri Nilfatri; Sayida Khoiratun Nisak; Alisyah Pitri; Hasna Dewi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Click here and insert abstract your text. Insert an abstract of 200-300 words, giving a brief account of the most relevant aspects of the paper. The study purpose was … Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Materials and methods. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Results. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Conclusions. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text. Click here and insert your text.